Application of the 3R Concept in the Production of European Antiviperinum on Horses – Multisite, Low Volumes Immunization Protocol and Elisa - Milovanović Vladimir (Sciendo, 2018)
During time, both professionals and general public became aware of the importance of animal welfare. This term not only covers endangered wild animal species, animals used in food industry, pets and experimental animals, but also animals used in production of biologics. The implementation of the 3R concept (Replacement, Reduction and Refinement) is especially important in this type of production. In this article, we describe for the first time the low dose, low volume and multi-site immunization protocol, as well as appropriate ELISA we developed for production of European anti-viper (V. ammodytes, long horned) antivenom in horses, which can help to significantly improve the welfare of the used animals.